Asymptotics for the Moment Convergence of U-Statistics in LIL. (2nd February 2010) - Fu, Ke-Ang
Abstract : LetU n be aU -statistic based on a symmetric kernelh ( x, y ) and i.i.d. samples X, X n ; n ≥ 1 . In this paper, the exact moment convergence rates in the law of the iterated logarithm and the law of the logarithm ofU n are obtained, which extend previous results concerning partial sums.